Urgensi Perubahan Status Fungsi Kawasan Hutan Gunung Muria Menjadi Taman Hutan Raya - Novytasari, Puput; Sahara, Shanly Rizki; Marwa, Shofia Basari; Munajat, Mafut; Supriyadi, Supriyadi; Agustina, Ana; Wicaksono, Rezky Lasekti (Konservasi Hayati, 2024)
The Gunung Muria forest is one of the important ecosystem value areas in Central Java. This area is relatively well-maintained and in good condition. One strategy for enhancing the protection and preservation of the area is to elevate the status of the forest area's function from that of a protected forest and production forest to that of a nature conservation area within the context of a great forest park. This research is descriptive and exploratory with a qualitative approach. Primary data was obtained from interviews with key people and observations in the field. Secondary data was obtained from literature studies and document studies from related agencies. Data analysis was conducted using a qualitative descriptive method supported by systematic data presentation. The important values of the change in the status of the Mount Muria forest area are 1) protection function, 2)biodiversity, 3) important bird area, and 4) cultural identity. The results show that the Mount Muria forest ecosystem serves as a vital component in the maintenance of the life-support system, acting as a natural barrier for 11 upstream watersheds. The area has high biodiversity and habitat for protected and endangered wildlife. The conversion of the Gunung Muria forest region into a forest park is planned to protect endemic wildlife, specifically the Javan leopard, and their ecology. This change's effectiveness depends on careful planning, community participation, and support from many stakeholders.